2000
DOI: 10.1034/j.1600-0773.2000.pto860502.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Prooxidative Action of Stilbene Derivatives

Abstract: The effects of stilbene derivatives, including resveratrol, diethylstilboestrol and stilbene, as antioxidants or prooxidants were examined. Resveratrol and diethylstilboestrol, but not stilbene, strongly inhibited NADPH-and adenosine 5ø-diphosphate (ADP)-Fe 3π -dependent lipid peroxidation at the initial and propagation stages. In addition, phenolic stilbenes also inhibited ultraviolet light-induced lipid peroxidation. Resveratrol and diethylstilboestrol efficiently scavenged 2,2ø-azobis-(2-amidinopropane)-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…We observed a rapid enhancement in ROS production (Pte from 0 to 160 mM) and GSH depletion (Pte from 80 to 160 mM) as a preliminary effect of Pte-induced HeLa cell apoptosis, in agreement with previously published pro-apoptotic reports in other cell lines (21,45,46). Stilbenes, including Pte, have also been reported to generate ROS and electrophilic molecules (19,21,47). Nevertheless, other research has revealed that Pte shows highly efficient anti-oxidative activities against several types of ROS (48).…”
Section: Discussionsupporting
confidence: 79%
“…We observed a rapid enhancement in ROS production (Pte from 0 to 160 mM) and GSH depletion (Pte from 80 to 160 mM) as a preliminary effect of Pte-induced HeLa cell apoptosis, in agreement with previously published pro-apoptotic reports in other cell lines (21,45,46). Stilbenes, including Pte, have also been reported to generate ROS and electrophilic molecules (19,21,47). Nevertheless, other research has revealed that Pte shows highly efficient anti-oxidative activities against several types of ROS (48).…”
Section: Discussionsupporting
confidence: 79%
“…Oxidation of LDL cholesterol is strongly associated with risk of CVD (Holvoet, 2004). In this regard, resveratrol was found in rat liver microsomes to inhibit iron-induced, as well as ultraviolet-irradiated, lipid peroxidation and to prevent LDL oxidation by copper (Fauconneau et al, 1997;Miura et al, 2000); moreover, Rocha et al found a reduction in oxidized LDL in rats fed on a high fat diet when treated with resveratrol for 45 days at a dose of 1 mg/kg BW/day .…”
Section: Antioxidant Properties Of Resveratrolmentioning
confidence: 99%
“…Iron plays a crucial role in free radical reactions leading to iron-oxygen complexes that remove hydrogen atoms from the polyunsaturated fatty acid membrane (Minotti and Aust 1989;Sotomatsu et al, 1990;Rice-Evans and Burdon 1993). Miura et al (2000) found that resveratrol possesses both antioxidant and pro-oxidant effects. Resveratrol promoted the reduction of Fe 3+ by increasing the formation of hydroxyl radicals through the Fenton reaction producing hydroxyl radicals and iron species (Yamazaki and Piette 1990).…”
Section: +mentioning
confidence: 99%